The Research Trends in History Education Across Several Countries - Khoeriyah, Ngismatul; Winoto, Darmawan Edi (CV. ULIL ALBAB CORP, 2025)
This study systematically examined global trends in history education by analyzing 32 scholarly articles published between 2020 and 2024. The review identified a significant shift from traditional pedagogical methods to more contextual, transformative, and technology-driven approaches. It emphasized the necessity of integrating local knowledge, adapting to cultural values, and utilizing digital technology to enhance the quality of history education. Furthermore, the findings indicated that the success of curriculum transformation depends on several factors, including policy support, educator training, and responsiveness to local and global needs. The research also acknowledged challenges associated with implementing transformative curricula, such as social inequalities and resistance to change. However, culturally based approaches, such as the application of the Kawa model in Lesotho and the promotion of national identity through local wisdom-based learning in Indonesia, demonstrated promising outcomes. This study underscored the importance of history education as a means of fostering critical thinking, cultural identity, and adaptability in students amid global challenges. Overall, the findings provide valuable insights into trends in history education and inform the development of curricula that are more relevant, inclusive, and sustainable.